Efferocytosis in tissue engineering: A comprehensive review of emerging therapeutic strategies for enhanced tissue repair and regeneration - Yue-Qi Zhang; Rong Nie; Zi-Yuan Feng; Ming-Hui Fan; Zhi-Xue Shen; Xiu-Zhen Zhang; Qing-Yi Zhang; Chen-Yu Zou; Ji-Ye Zhang; Kai Huang; Li-Ping Mou; Hui-Qi Xie (Bioactive Materials)
Abstracts: This comprehensive review elucidates the critical role of efferocytosis in tissue repair and regeneration processes, while systematically exploring innovative approaches through which tissue engineering strategies can modulate efferocytosis to optimize these biological processes. The manuscript is structured to first establish a fundamental understanding of efferocytosis, encompassing its core concepts, molecular mechanisms, and physiological functions within tissue repair. Subsequently, it provides an in-depth analysis of the regulatory role of efferocytosis in inflammatory response modulation during tissue repair cascades. The review culminates in a detailed investigation of cutting-edge tissue engineering applications specifically designed to manipulate efferocytosis pathways. Substantial evidence from recent studies has unequivocally demonstrated that efferocytosis serves as a crucial biological process in maintaining tissue homeostasis and orchestrating injury repair mechanisms. In this context, tissue engineering has emerged as a transformative approach, offering precise control over efferocytosis enhancement, inflammation resolution, and tissue regeneration processes. Through sophisticated integration of bioactive factor regulation, advanced scaffolding materials, and targeted cellular interactions, tissue engineering platforms have established novel therapeutic paradigms, providing unprecedented insights and innovative strategies for the treatment of diverse pathological conditions.